Lipid Abnormalities Using Random Sampling In Patients With End Stage Renal Disease On Thrice Weekly Hemodialysis - Anwar, Shahid; Zainab, Alvina; Mazhar, Sobia (Pakistan Journal of Kidney Diseases, 2021)
Background: Cardiovascular disease (CVD) is the leading cause of death in the dialysis population. Among other risk factors abnormalities in lipid metabolism occur in patients with all stages of chronic kidney disease (CKD). The most common dyslipidemia in CKD and dialysis is hypertriglyceridemia, whereas the total cholesterol concentration can be normal or low, perhaps due in part to malnutrition. Although hypertriglyceridemia that occurs in CKD may not significantly increase coronary risk, other changes may contribute to the accelerated atherosclerosis. We tried to find out how many patients in our setup on thrice weekly hemodialysis are suffering from dyslipidemia and whether taking treatment or not. Methodology: Cross sectional study conducted at dialysis center of Sir Ganga Ram Hospital, Lahore including all seventy patients with ESRD undergoing regular HD three times a week, 4 hours per session. Random blood samples (Non-fasting) were collected before dialysis for lipid profile including serum triglyceride, LDL, HDL and total cholesterol. Results: Out of 70 patients only 3 (4.4%) patients were on statins for dyslipidemia. Triglycerides were high in 41.4%, total cholesterol was low in 61.4%, and HDL was low in 34.3%. Conclusion: Hypertriglyceridemia is major lipid abnormality among hemodialysis patients.